Medicinal plants used in Soran district Kurdistan region of Iraq, an ethnobotanicals study - Abdulwahid-Kurdi, Samiaa J.; Abdulwahid, Muhsin J.; Magaji, Usman; Aghwan, Zeiad A.; Atan, Rodziah; Hamadamin, Kasrin A. (Frontiers Media SA, 2022)
The current study, the first of its type, focuses on the ethnobotanical uses of 97 medicinal plant species by the inhabitants in the Soran area, Kurdistan region of Iraq. Aims: To evaluate local knowledge of medicinal plants and provision of preliminary data on the user-benefit of the accessible plant species in the area. Methods: Between October 2021 and May 2022, key informant interviews were conducted as part of an ethnobotanical survey. Information about a particular study through face-to-face interviews with 171 participants (98 males and 73 females) were collected. For the therapeutic plants considered in the study, quantitative indices such as use value (UV), family use value (FUV), the relative frequency of citation (RFC), fidelity level (FL), and informant consensus factor (ICF) were applied in addition to detailed notes on each plant species. Results: The survey discovered 97 plant species and 41 plant families. Leaves were the plant portion that was used the most (44%) while seeds were the least (12%). The most popular three methods of preparation were decoction (52%), row (36%), and crushed (6%). The Olea europaea species had the highest use values (0.82), while Vitex agnus-castus had (0.005). Amaryllidaceae had the highest family use value (1.218), while Asteraceae had (0.005). According to the consensus index, Ficus carica and Datura stramonium had (140.84%) and (1.011%). The digestive tract disease category was shown to have the highest informant consensus factor value out of all disease categories (0.57), while the lowest value ICF was (0.0) for tooth pain. Conclusions: As a result of the development of natural medicines, this study gives information on the indigenous medicinal plants utilized in the Soran district to treat common illnesses that are ready for additional pharmacological and phytochemical examination. For better use of natural resources, the traditional use of plants requires conservation methods and additional research.